The use of antimicrobials to boost livestock productivity at Ugandan piggery and poultry farms and implications for public health - Ndoboli, D.; Lukuyu, Ben A.; Wieland, Barbara; Grace, Delia; Roesel, Kristina (2019)
Improving productivity is a major challenge for livestock keepers in Uganda. According to anecdotal newspaper reports, pig and poultry keepers from Uganda have been using various antimicrobial substances for growth promotion in pigs and poultry that are banned for livestock use, such as anti- retroviral drugs (ARV). A qualitative study in ten districts across Uganda aimed to determine farmers’ perceptions and practices related to antimicrobials. Two focus group discussions (FGD) were conducted each district, one including eight pig and poultry farmers known for feeding antimicrobials who were recruited with the help of the district veterinary officers; and one with a group of animal health workers serving the same geographical area. A generic tool (KAP AMUSE) to assess knowledge, attitudes and practices on antimicrobial use guided the development of a group discussion protocol. In addition, in each district, samples of chicken (n=100), pigs (n=100) and animal feeds (n=50) were collected for screening of antibiotic residues using Premi®Test (r-biopharm, Germany) and for residues of antiretrovirals using high-performance liquid chromatography. Feeds and diseases were the main challenges faced by farmers. All poultry farmers, from small to large size flocks, reported adding antibiotics to water and feeds to prevent disease. Pig farmers reported limited use of antibiotics, but in the event of African swine fever outbreaks, they use a lot of oxytetracycline for treatment. Farmers reported the use of ARVs as growth promoters, an idea that developed from the fact that ARVs seem to cause rapid weight gain in humans. Farmers also reported the use of ARVs to manage viral infections in poultry and pigs, apparently because to them virus of humans and livestock of the same family and if ARVs “can relive the viral infections in humans, they ought to perform wonders with livestock virus”. The work is co-funded by the CGIAR Research Program on Livestock and on Agriculture for Nutrition and Health as part of a fellowship with the Africa Biosciences Challenge Fund at the Biosciences eastern and central Africa Hub hosted by ILRI in Nairobi.